Identification of a novel broad-spectrum endolysin, Ply0643, with high antibacterial activity in mouse models of streptococcal bacteriaemia and mastitis. (March 2022) - Liu, Guangjin; Zhang, Shiyu; Gao, Tingting; Mao, Zhao; Shen, Yanling; Pan, Zihao; Guo, Changming; Yu, Yong; Yao, Huochun
Abstract: Streptococcal infections are very common in humans and animals, and they are usually treated with antibiotics. Multidrug-resistant Streptococcus strains have continuously emerged in recent years, prompting the search for alternatives to antibiotics. The use of endolysins encoded by phages has presented a promising alternative approach to treatment. In this study, a novel prophage endolysin, Ply0643, was identified from the prophage S. a 04. At an optimal concentration (30 μg/mL ), rPly0643 exhibited broad and strong lysosomal enzyme activity against 66 Streptococcus strains from different sources while also maintaining high lytic activity over a wide pH range (pH 6–10) and a broad range of temperatures (28 °C–45 °C). Two in vivo treatments of rPly0643 (total 0.8 mg/mouse) significantly protected mice (80%) from lethal bacteriaemia with Streptococcus suis, and single treatments of rPly0643 (0.1 mg/gland) significantly reduced Streptococcus agalactiae concentrations and inflammation in murine mammary glands. These findings collectively demonstrate that Ply0643 exhibits good bactericidal activity both in vitro and in vivo, and therefore represents a useful antibacterial agent for combatting streptococcal infections. Highlights: Characterization of a novel endolysin Ply0643 with broad lysis against streptococcus spp. Ply0643 plays a vital role in lysis activity depended on its full length. rPly0643 has excellent therapeutic effects in the infected murine models of streptococcal bacteremia and mastitis.